Pd-catalyzed γ-C(sp(3))–H Arylation of Free Amines Using a Transient Directing Group - Wu, Yongwei (J Am Chem Soc, 2016)
Pd(II)-catalyzed γ-C(sp(3))–H arylation of primary amines is realized by using 2-hydroxynicotinaldehyde as a catalytic transient directing group. Importantly, the catalyst and the directing group loading can be lowered to 2% and 4% respectively, thus demonstrating high efficiency of this newly designed transient directing group. Heterocyclic aryl iodides are also compatible with this reaction. Furthermore, swift synthesis of 1,2,3,4-tetrahydronaphthyridine derivatives is accomplished using this reaction.